Telomere Shortening in Hypertensive Heart Disease Depends on Oxidative DNA Damage and Predicts Impaired Recovery of Cardiac Function in Heart Failure. Issue 10 (18th July 2022) - Brandt, Moritz; Dörschmann, Hendrik; Khraisat, Sana'a; Knopp, Tanja; Ringen, Julia; Kalinovic, Sanela; Garlapati, Venkata; Siemer, Svenja; Molitor, Michael; Göbel, Sebastian; Stauber, Roland; Karbach, Susanne Helena; et al.
Abstract : Background: Heart failure (HF) coincides with cardiomyocyte telomere shortening. Arterial hypertension is the most prominent risk factor for HF. Both HF and arterial hypertension are associated with dysregulation of the neurohormonal axis. How neurohormonal activation is linked to telomere shortening in the pathogenesis of HF is incompletely understood. methods: Cardiomyocyte telomere length was assessed in a mouse model of hypertensive HF induced by excess neurohormonal activation (AngII [angiotensin II] infusion, high salt diet, and uninephrectomy), in AngII-stimulated cardiomyocytes and in endomyocardial biopsies from patients with HF. Superoxide production, expression of NOX2 (NADPH oxidase 2) and PRDX1 (peroxiredoxin 1) and HDAC6 (histone deacetylase 6) activity were assessed. Results: Telomere shortening occurred in vitro and in vivo, correlating with both left ventricular (LV) dilatation and LV systolic function impairment. Telomere shortening coincided with increased superoxide production, increased NOX2 expression, increased HDAC6 activity, loss of the telomere-specific antioxidant PRDX1, and increased oxidative DNA-damage. NOX2 knockout prevented PRDX1 depletion, DNA-damage and telomere shortening confirming this enzyme as a critical source of reactive oxygen species. Cotreatment with the NOX inhibitor apocynin ameliorated hypertensive HF and telomere shortening. Similarly, treatment with the HDAC6 inhibitor tubastatin A, which increases PRDX1 bioavailability, prevented telomere shortening in adult cardiomyocytes. To explore the clinical relevance of our findings, we examined endomyocardial biopsies from an all-comer population of patients with HF with reduced ejection fraction. Here, cardiomyocyte telomere length predicted the recovery of cardiac function. Conclusions: Cardiomyocyte telomere shortening and oxidative damage in heart failure with reduced ejection fraction induced by excess neurohormonal activation depends on NOX2-derived superoxide and may help to stratify HF therapy.